Executive control of freestyle skiing aerials athletes in different training conditions - Li, Hui; Zhang, Liancheng; Wang, Jingru; Liu, Jie; Sun, Yanlin (Frontiers in Psychology, 2022)
Introduction: Due to the actual limitation of training conditions, the freestyle skiing aerials winter training term is short. Training tasks such as adaptability training and developing new skills are needed in summer training. When facing different training environments, freestyle skiing aerial athletes’ executive control over their abilities could be affected, which can affect their performance. Therefore, we want to research the effect of training conditions on executive control in freestyle skiing aerials athletes. Methods: Thirty-two freestyle skiing aerials athletes were recruited. We evaluated their behavioural performance and used fNIRS to measure oxygenated haemoglobin concentration changes in the prefrontal cortex during a rapid event-related design go/no-go task with different training condition-activated materials. Results: Athletes' behaviour control in the summer condition has a lower accuracy than it is in the control condition. Athletes' behaviour control in the summer and winter training conditions had a longer reaction time than that in the control condition. The activation of the bilateral dlPFC and orbitofrontal cortex had a significant main effect across training conditions when freestyle skiing aerial athletes completed executive control tasks. The activation of athletes’ bilateral vlPFC and left dlPFC had an interaction between training conditions and behavioural control. Conclusions: Different training conditions can lead to freestyle skiing aerial athletes executive control ability to drop, players in different training conditions show less activation on both sides of the vlPFC and orbitofrontal. The bilateral vlPFC and left dlPFC have an integrated effect on behaviour inhibition across training conditions.